Research into parameters of energy loss when trains influence the track with wooden sleepers - Tuley, Yusef; Bugaets, Natalia; Malishevskaya, Alina (Eastern-European Journal of Enterprise Technologies, 2016)
The magnitude that quantitatively characterizes the process of interaction between the track and the rolling stock was determined as equivalent coefficient of dissipation (ECD). This coefficient, as an estimated magnitude, takes into account all kinds of friction forces in the process of dissipation – the forces of dry friction that depend on the deformation of the track structure, as well as viscous friction forces that depend on deformation velocity, and, possibly, other types of friction forces. These forces exert considerable effect on the characteristics of strength of a railway track and, therefore, on the safety of motion, which is why the research in this paper is quite relevant. Theoretical positions are presented that allow us to determine a mathematical formula for the calculation of ECD for rail supports of railway track. We detected the values of vertical and horizontal transverse ECD for the wooden sleepers, for which we used data of experimental studies carried out at 12 sections of Ukrainian railways with different operational conditions. Based on these data, dependence was established of ECD of rail supports in the vertical and horizontal plane on the magnitude of tonnage that passed the track. Results of the experiments indicate that with an increase in tonnage from 0 to 300 million tons, values of coefficients of dissipation in the vertical plane increase by 1.5–1.9 times, and in the horizontal plane – by about 1.3 times. Based on the aforementioned, there is a possibility of practical use of ECD to determine the current state of the track and a need for repair work.